Actuarial Adjustments, Retirement Behaviour and Worker Heterogeneity - Matthias Giesecke (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2014)
The behavioural response with respect to actuarial adjustments in the German public pension system is analysed. The introduction of actuarial adjustments serves as a source of exogenous variation to estimate discrete time transition rates into retirement. The analysis is conducted on administrative data from social security records and on survey data in a comparative scenario. Probability mass points that occur for institutional reasons and due to social norms are controlled for. Moreover, worker heterogeneity is taken into account, which has not been addressed in the previous literature. The results show that on average retirement is postponed by five months due to financial incentives via actuarial adjustments. However, this response is about 40 per cent lower for manual workers compared to non-manual workers which indicates that their retirement income may deteriorate. – – Die Studie untersucht die Verhaltensreaktion auf finanzielle Anreize hinsichtlich des Renteneintrittsalters. Die Einführung versicherungsmathematischer Abschläge dient als Quelle exogener Variation, um Renteneintrittsraten in diskreter Zeit zu schätzen. Die Analyse basiert auf Administrativdaten der Deutschen Rentenversicherung (VSKT) sowie Umfragedaten des Sozioökonomischen Panels (SOEP) um mögliche Unterschiede in den Ergebnissen aufgrund der Datenmenge und Datenqualität in einem komparativen Szenario zu kontrollieren. Ein besonderer Fokus in der Analyse des Renteneintrittsverhaltens liegt auf individueller Heterogenität hinsichtlich des physischen Anspruchs ehemals ausgeübter Berufe. Die Ergebnisse zeigen, dass die Einführung versicherungsmathematischer Abschläge in Deutschland zu einer durchschnittlichen Verzögerung des Renteneintritts um fünf Monate führt. Diese Reaktion auf finanzielle Anreize ist bei Individuen mit ehemals physisch anspruchsvollen Berufen jedoch etwa 40% niedriger.
Keywords: C41; H55; J26; 330; natural experiment; actuarial adjustments; retirement; worker heterogeneity